Risk-Oriented Approach as the Basis for the Corporate Accounting Policy Formation - V. M. Rumyantseva (Учёт. Анализ. Аудит, 2018)
The evolution of accounting and reporting, the relevance of risk orientation as the basis for the organization of accounting and control processes involves the expansion of ideological fundamentals of the formation of corporate level accounting policy. The risk-oriented approach should be the basis of accounting and control processes of any economic entity. That is why, it is the risk-oriented approach that should be the basis for formation of the accounting policies and internal control systems of the economic entity. In the corporate structure the risks related to corporate governance are particularly important. Therefore, corporate accounting policy, while expanding its borders, must take into account corporate risks related to inter-group relationships. Through the formation of and disclosure of corporate accounting policy the planning and control of joint activities is implemented, which involves analysis and monitoring of strategic risks. Risk-oriented corporate accounting policies, being the regulator of corporate relationships through the implementation of the managerial function can influence the effectiveness of corporate integration. Corporate accounting policy may be the means of achieving the synergy effect in the enterprise integration by defining and regulating the most efficient forms of interaction of the reproduction process members. The evolution of accounting policies closely associated with the evolution of accounting and reporting, leads to the need to identify the relationship of accounting policies and internal control systems at all levels of corporation government, because it is the accounting policy that determines the intra firm accounting principles and is the regulator of corporate relations at all levels of corporate governance. Monitoring of accounting policy, based on the principle of materiality is key to both the separate legal entity that is the part of the group, and to the entire perimeter of consolidation. Key risks relate to the concept of materiality and correspond to the key issues of the auditing that is relevant in the context of the new requirements of the international auditing standards.